Difficult Cases in Robotic Arm-Assisted Total Knee Arthroplasty: A Case Series - Marchand, Robert C.; Khlopas, Anton; Sodhi, Nipun; Condrey, Caitlin; Piuzzi, Nicolas S.; Patel, Rickesh; Delanois, Ronald E.; Mont, Michael A. (The Journal of Knee Surgery, 2018)
Sagittal deformity of the knee is commonly corrected to neutral biomechanical axis (±3 degrees) during total knee arthroplasty (TKA), which is a widely accepted goal. Recent advances in surgical technology have made it possible to accurately plan and fulfill these goals. One of these is robotic-assisted TKA, which has been noted to help increase accuracy and precision of restoring a neutral mechanical axis. While there are data confirming the ability of robotic devices to better correct knee alignment than the manual technique, there is a lack of data concerning the use of the robotic devices in more complex cases, such as those in patients with severe varus or valgus deformity, as well as in flexion contractures. Therefore, the purpose of this case study is to present three cases in which the robotic-assisted TKA device was used to correct a severe varus and severe valgus deformities. Based on this case series, it should be noted that the robotic device can also help correct severe varus/valgus deformities and flexion contractures.
Keywords: total knee arthroplasty; robotic total knee arthroplasty; difficult cases; varus; valgus